The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s13102-022-00403-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrode size and placement on comfort and efficiency during low-intensity neuromuscular electrical stimulation of quadriceps, hamstrings and gluteal muscles

Abstract: Background Neuromuscular electrical stimulation (NMES) may prevent muscle atrophy, accelerate rehabilitation and enhance blood circulation. Yet, one major drawback is that patient compliance is impeded by the discomfort experienced. It is well-known that the size and placement of electrodes affect the comfort and effect during high-intensity NMES. However, during low-intensity NMES the effects of electrode size/placement are mostly unknown. Therefore, the purpose of this study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…The electrode placement and size were based on a previous study comparing different pre-determined electrode configurations (Flodin et al 2022 ). Self-adhesive electrodes (Compex Snap, Performance, DJO Global, USA) were used to apply the NMES.…”
Section: Methodsmentioning
confidence: 99%
“…The electrode placement and size were based on a previous study comparing different pre-determined electrode configurations (Flodin et al 2022 ). Self-adhesive electrodes (Compex Snap, Performance, DJO Global, USA) were used to apply the NMES.…”
Section: Methodsmentioning
confidence: 99%
“…The higher frequencies within the range of 1-50 Hz, when using standard gel electrodes, have been suggested to reduce the current amplitudes required to produce muscle contraction (Baker et al 1993;Flodin et al 2022;Gobbo et al 2014;Mettler et al 2018). Previous studies which included evaluation of comfort have suggested a frequency of around 36 Hz to be comfortable while at the same time not causing excessive muscle fatigue (Baker et al 1993;Breen et al 2012;Broderick et al 2014;Lyons et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome that determined sample size was cumulative sufentanil equivalents at 24 postoperative hours. Additional analgesic measures were average pain scores at rest and on movement for both incision pain and intra‐abdominal pain to 24 h. Other outcomes were time to first participant‐administered sufentanil, the number of sufentanil boluses demanded and delivered within 48 h and the doses of additional analgesics to 48 h. We also recorded: the quality of recovery‐15 score at 24 h; sleep quality during the first two postoperative nights; nausea or vomiting to 48 h; complications; time to drain removal; time to ingestion and ambulation; time to hospital discharge; and estimated costs [24–26].…”
Section: Methodsmentioning
confidence: 99%